PENGELOLAAN SISTEM DRAINASE KAMPUS UNYKARANGMALANG MENUJU KEMANDIRIANSUMBER AIR BERSIH - Didik Purwantoro Sumardjo H, Rifta AP, Dwi Yulianto (Universitas Negeri Yogyakarta, 2012)
This research was meant to find out Capability of a system campusdrainage area at Universitas Negeri Yogyakarta, Karangmalang. Karangmalangbecomes very strategic because of An influence on the flooding during the rainSubsidence groundwater as a source of clean water in the summer. The colomboarea that is part of the campus Universitas Negeri Yogyakarta (the gate of UNY), aslong as it has been known as a flood-prone area. This research was conducted withsurvey approaches in the field for 4 months. The fist step, evaluation dischargeoccurring due to rain in kawasan UNY campus. The second evaluation of drainagechannels in the drain the ability of surface water with the rational method. The testresult showed that the drainage system Was not able to fulfill a discharge of waterthat occurs with 55,77mm/jam or Rain reëxamined high by period of 10 years. Butwhen most of the rain water (from roof) Distributed into infiltration well, therefore theneed of infiltration well as 388 pieces????Keyword: drainage, Universitas Negeri Yogyakarta